Unscheduled Departures: The Circumvention of Just Sentencing for Police Brutality - Freeman, Alexa P. (1996)
This Article examines the problems presented when courts depart downward from the federal sentencing guidelines in police brutality cases. Sentences for police officers increased following the enactment of the sentencing guidelines, which this Article attributes to two factors: the elimination of sentencing disparities between police and civilian crimes, and the assignment of additional penalties for the civil rights dimension of the crime. The author contends that, without sentencing guidelines, police brutality is not sentenced commensurate with the harm committed; judges were often constrained by community attitudes and norms, even when they recognized the problem and wanted to impose adequate terms of imprisonment. The author places police brutality and its causes in the larger context of race and ethnicity in the United States, especially the African-American relationship to the criminal justice system. However, the policy of fair punishment for police brutality achieved by the use of civil rights sentencing guidelines may be short-lived. In January 1995, the Sentencing Commission staff proposed that the Commission reduce the offense level for civil rights crimes committed under color of law and correspondingly reduce the sentence to be applied. In the June 1996 decision of Koon v. United States the Supreme Court upheld most of the departure grounds applied by the trial court in sentencing the two police officers convicted in the Rodney King beating. The Supreme Court's decision is troubling because it paves the way for downward departures from the sentencing guidelines in future police brutality cases. This action effectively sends a message to the police, and the nation, that police are above the law. This Article argues that the Sentencing Commission must act again to ensure that just sentencing for police brutality is maintained. The author recommends that the Commission act promptly, amending the guidelines to make clear that the departure grounds approved by the Supreme Court in Koon are not applicable in police brutality cases